Recommendations Related To Wheeze Sound Data Acquisition - Sundaraj, Kenneth; Nabi, Fizza Ghulam; Lam, Chee Kiang; Palaniappan, Rajkumar; Hussain, Jawad (Penerbit Universiti,UTeM, 2018)
In the field of computerized respiratory sounds,a reliable data set with a sufficient number of subjects is required for the development of wheeze detection algorithm or for further analysis.Validated and accurate data is a critical issue in the field of research.In this study,the protocol related to wheeze sound data acquisition is discussed.Previously,most articles focused on wheeze detection or its parametric analysis,but no consideration was given to data acquisition.Second major purpose of this study is to exhibit particulars of our dataset which was attained for future analysis.We compile a database with a sufficient and reliable number of cases with all essential details,in contrast to commercially available wheeze sound data used for research,freely available online data on websites and data used to train medical students for auscultation.